Represenasi Citra Positif Islam dalam film Kingdom of Heaven - Jalaluddin nahrawi; Nabilla Puti Syafira (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
After the bombing of the World Trade Center (WTC) building in 1993, Hollywood has intensively produced films which have laid the blame of terrorist acts in the United States on Muslims. These films give a bad image to Muslims,particularly after the 2001 WTC bombing by Al-Qaeda.It was reported that the leading print media increased their reportage of news about Islam by 560%. After the events of 9/11, the issue of Islamophobia again became a hot issue not only in America, but also in countries with a small Muslim populations. Uniquely, four years later, Hollywood released the movie Kingdom of Heaven film which gives a more positive image of Islam. The film tries to counter the negative stigma of Westerners of the teachings of Islam, as well as educate the international community on true teachings of Islam through the story of Saladin's generosity while leading the Islamic forces during the Crusading era. This study aims to determine the meaning of the denotations, connotations, and myths of the signs that exist in the film Kingdom of Heaven on the positive image of Islam presented in it. This research method is a qualitative interpretive and semiotics analysis of Roland Barthes. The results of research ison six analysis units in the form of scenes in Kingdom of Heaven which show a positive image of Islam successfully portrayed in the film.